MIDWIFERY CARE MANAGEMENT OF PREGNANT WOMEN WITH HEMORRHOIDS AT HAJI MEDAN HOSPITAL 2025 - Mumthanna, Siti Yupa; Br Saragih, Salwa Adya Mecca; Hutapea, Riska; Harahap, Aylinda; Damanik, Nopalina Suyanti; Widianti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Hemorrhoids are one of the most common anorectal disorders experienced during pregnancy, particularly in the third trimester. Physiological and hormonal changes during pregnancy increase the risk of constipation, which contributes to the development of hemorrhoids. This condition may cause pain, rectal bleeding, discomfort, and decreased quality of life in pregnant women. Early detection and appropriate management are important to prevent complications and improve maternal well-being. Objectives: To describe the management of midwifery care for a pregnant woman with hemorrhoids at Haji General Hospital Medan in 2025. Methods: This study employed a descriptive case study approach. Data were collected through interviews, physical examinations, observation, and review of medical records. Midwifery management was carried out using the Varney Midwifery Management Process. Results: Mrs. M, 32 years old, G2P1A0, at 34 weeks of gestation, presented with complaints of rectal bleeding, anal pain, constipation, and weakness. Physical examination showed blood pressure 90/70 mmHg, pulse 96 beats/minute, respiratory rate 20 breaths/minute, and temperature 36°C. A hemorrhoidal mass with fresh rectal bleeding was observed. Midwifery care included assessment of maternal condition, monitoring of vital signs, pain management, observation of bleeding, health education regarding hemorrhoids, dietary counseling with increased fiber and fluid intake, and collaboration with physicians for further management. Conclusions: Comprehensive midwifery care and collaborative management are essential in reducing symptoms, preventing complications, and improving the quality of life of pregnant women with hemorrhoids.